x-y=4, x2-xy=12

x - y = 4, x = y + 4 (equation 1) x^2 - xy = 12 (equation 2) replace x in the equation 2 we get: (y + 4)^2 -y(y +4) = 12 y^2 + 8y + 16 - y^2 - 4y = 12 4y = 12 - 16 = -4 y = -1 x = -1 + 4 = 3 The solution is (3, -1)

Question

Asked 11/22/2009 11:20:52 AM

Updated 4/15/2014 8:18:21 AM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

8

x - y = 4, x = y + 4 (equation 1)

x^2 - xy = 12 (equation 2)

replace x in the equation 2 we get:

(y + 4)^2 -y(y +4) = 12

y^2 + 8y + 16 - y^2 - 4y = 12

4y = 12 - 16 = -4

y = -1

x = -1 + 4 = 3

The solution is (3, -1)

x^2 - xy = 12 (equation 2)

replace x in the equation 2 we get:

(y + 4)^2 -y(y +4) = 12

y^2 + 8y + 16 - y^2 - 4y = 12

4y = 12 - 16 = -4

y = -1

x = -1 + 4 = 3

The solution is (3, -1)

Added 4/15/2014 8:18:21 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/15/2014 8:21:54 AM]

36,651,984

questions answered

There are no comments.